Conventional Wisdom, Meta-Analysis, and Research Revision in Economics - Sebastian Gechert; Bianka Mey; Matej Opatrny; Tomas Havranek; T. D. Stanley; Pedro R. D. Bom; Hristos Doucouliagos; Philipp Heimberger; Zuzana Irsova; Heiko J. Rachinger (ZBW - Leibniz Information Centre for Economics, 2023)
Over the past several decades, meta-analysis has emerged as a widely accepted tool to understand economics research. Meta-analyses often challenge the established conventional wisdom of their respective fields. We systematically review a wide range of influential meta-analyses in economics and compare them to `conventional wisdom.' After correcting for observable biases, the empirical economic effects are typically much closer to zero and sometimes switch signs. Typically, the relative reduction in effect sizes is 45-60%.
Keywords: A14; B40; C10; 330; meta-analysis; systematic review; conventional wisdom